2001
DOI: 10.1046/j.1365-2591.2001.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro evaluation of the antimicrobial efficacy of irrigants on biofilms of root canal isolates

Abstract: The effectiveness of a particular agent was dependent on the nature of the organism in the biofilm and on the contact time. NaOCl was generally the most effective agent tested, followed by iodine. However the clinical efficacy of these agents must be considered in light of the complex root canal anatomy and polymicrobial nature of root canal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
190
3
33

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(232 citation statements)
references
References 41 publications
6
190
3
33
Order By: Relevance
“…NaOCl with different concentrations lead to contradictory results. For instance, in the study by Spratt et al, using NaOCl 3% resulted in complete elimination of E. faecalis 63 which is contrary to the results of the present study.…”
Section: Anti-bacterial Effect Of Er:yag Laser On Enterococcus Faecaliscontrasting
confidence: 99%
“…NaOCl with different concentrations lead to contradictory results. For instance, in the study by Spratt et al, using NaOCl 3% resulted in complete elimination of E. faecalis 63 which is contrary to the results of the present study.…”
Section: Anti-bacterial Effect Of Er:yag Laser On Enterococcus Faecaliscontrasting
confidence: 99%
“…faecalis is an important opportunistic pathogen having the ability to adhere to biotic and abiotic surfaces allowing the formation of a biofilm that permits to grow and survive in harsh environments prevailing in the root canal (12,14,17). A number of infections caused by E.faecalis strains have proven to be particularly difficult to treat with current antibiotic therapies, partly owing to their intrinsic antibiotic resistance elements, capacity of growing in a biofilm (24). It has gained notoriety as a persistent organism that can survive as a monoculture in root canals (20).…”
Section: Discussionmentioning
confidence: 99%
“…All the irrigants used are known to have antimicrobial properties however; they have differing efficacies with respect to different microbiai species. Although sodium hypochlorite (NaOCl) has been shown to totally eradicate E. IaecaLis either as a planktonic form or as biofilm (34). It might also be advisable to use chlorhexidine and iodine for irrigation as several in vitro studies have reported ability of these irrigants to eradicate t.Iaecalis (34,35,47).…”
Section: Discussionmentioning
confidence: 99%
“…Although sodium hypochlorite (NaOCl) has been shown to totally eradicate E. IaecaLis either as a planktonic form or as biofilm (34). It might also be advisable to use chlorhexidine and iodine for irrigation as several in vitro studies have reported ability of these irrigants to eradicate t.Iaecalis (34,35,47). These results !lOwever may be confounded by the variation in root canal anatomy and polymicrobial root canal flora.…”
Section: Discussionmentioning
confidence: 99%